2015
DOI: 10.1016/j.epsl.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Eskers in a complete, wet-based glacial system in the Phlegra Montes region, Mars

Abstract: This paper investigates the influences of palaeohydrology and geologicaltopographic inheritance in shaping the channel of the lower River Suir, southeast Ireland. Results of acoustic surveys of the lower River Suir and Waterford Harbour reveal two scales of pseudo-cyclic river bedforms. Longitudinal elevation profiles of the geological topography (undulating bedrock and till-mantled bedrock) bounding the present floodplain swath reveal pseudo-cyclicity in that terrain too. Spectral and statistical analyses are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 76 publications
(55 reference statements)
3
48
0
Order By: Relevance
“…The lack of morphological evidence for prolonged supraglacial or subglacial melting (e.g., supraglacial channels, fans, and streamlined bedforms) leads us to exclude such a regional climate anomaly as the sole driver of wet‐based glaciation in the Tempe Terra rift. Thus, while we do not exclude climate warming as a possible contributing factor in inducing wet‐based glaciation, we argue that perturbation of basal ice temperatures by a geothermal heat flux anomaly (Gallagher & Balme, ) is more consistent with the tectonic setting and our geomorphic observations.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The lack of morphological evidence for prolonged supraglacial or subglacial melting (e.g., supraglacial channels, fans, and streamlined bedforms) leads us to exclude such a regional climate anomaly as the sole driver of wet‐based glaciation in the Tempe Terra rift. Thus, while we do not exclude climate warming as a possible contributing factor in inducing wet‐based glaciation, we argue that perturbation of basal ice temperatures by a geothermal heat flux anomaly (Gallagher & Balme, ) is more consistent with the tectonic setting and our geomorphic observations.…”
Section: Discussionmentioning
confidence: 53%
“…The lack of morphological evidence for prolonged supraglacial or subglacial melting (e.g., supraglacial channels, fans, and streamlined bedforms) leads us to exclude such a regional climate anomaly as the sole driver of wet-based glaciation in the Tempe Journal of Geophysical Research: Planets 10.1002/2017JE005434 Terra rift. Thus, while we do not exclude climate warming as a possible contributing factor in inducing wetbased glaciation, we argue that perturbation of basal ice temperatures by a geothermal heat flux anomaly (Gallagher & Balme, 2015) is more consistent with the tectonic setting and our geomorphic observations. While primary geothermal anomalies associated with the formation of the ancient rift in Tempe Terra (Hauber et al, 2010) are unlikely to have persisted into the Amazonian, magmato-tectonic processes could have exploited preexisting structural weaknesses in their vicinity to induce geothermal anomalies coincident with recent glaciation.…”
Section: Geologic Setting and Environmental Controls On Meltingmentioning
confidence: 47%
See 1 more Smart Citation
“…The planform geometry of these ridges is strong evidence that they are depositional channel systems now preserved as inverted relief (inverted fluvial channels; Burr et al, ; Davis et al, ; Pain et al, ; Williams et al, ). These ridges are interpreted as inverted fluvial channels rather than glacial eskers as they conform to regional topography (i.e., they do not go upslope) and lack associated glacier landforms commonly found with eskers (e.g., Butcher et al, ; Gallagher & Balme, ). Alternatively, the ridges may be the eroded remnants of erosional valley walls; however, given that multiple tributary ridges converge in the downslope direction, they are more consistent with inverted channels.…”
Section: Observationsmentioning
confidence: 99%
“…Sublimation of glacial ice (e.g., as dry ablation hollows; Mangold, ) would indeed leave a rimmed depression, but only if some material had accumulated along the ice margins, for example, as ice‐sediment contact or drop moraines at the margins of cold‐based glaciers (Atkins, ). If there was ever any glacial ice, it would probably have been cold based as no proglacial or glaciofluvial features such as channels or eskers (Fassett et al, ; Gallagher & Balme, ) were observed. A repeated sequence of past ice accumulation and sublimation could explain the nested occurrence of pits (Figure a).…”
Section: Discussionmentioning
confidence: 99%